Genetic divergence for yield and yield attributes in tomato (Solanum lycopersicum) - B L NAVEEN; K RAVINDER REDDY; P SAIDAIAH (The Indian Journal of Agricultural Sciences, 2018)
The research experiment was conducted to study genetic diversity for quantitative and qualitative traits in tomato (Solanum lycopersicum L.). The investigation was conducted during rabi, 2015-16 at Vegetable Research Farm, College of Horticulture, Rajendranagar, Hyderabad. Using Mahalanobis D2 statistic, the 30 genotypes were grouped into eight clusters, indicating the presence of diversity for different traits. The cluster I had the highest number containing 19 genotypes followed by cluster II containing five genotypes. However, the cluster III, IV, V, VI, VII and VIII were solitary. The maximum intra-cluster distance was recorded within cluster II (64.36) and the maximum inter-cluster distance between cluster VII and VI (220.70), indicating the existence of wide genetic variability. Based on mean performances, cluster III registered maximum plant height (134.40 cm). The genotypes included in clusters I took less number of days to first flowering (28.60), cluster III took less number of days to 50% flowering (35.33) and cluster I took less number of days to fruit set (38.33). The cluster VII registered high number of fruits per plant (326.00) and high fruit yield per plant (1.54 kg). The genotypes included in clusters I had maximum average fruit weight (51.23 g). The cluster V registered high TSS (9.07 oBrix). The cluster I registered high content of ascorbic acid (32.38 mg/100g) and beta carotene (2.33 mg/100g). Hence, these characters can be utilized in breeding programme for enhancing their respective characters. Based on cluster mean analysis, the superior and genetically divergent genotypes can be used in crop improvement programme in tomato.